Tourism Satellite Account Support Using Online Analytical Processing. (January 2016) - Giannopoulos, Konstantinos; Boutsinas, Basilis
The 10 tables in the Tourism Satellite Account (TSA) framework store a significant amount of data. These data when broken down are able to support significantly more statistical analysis. However, sophisticated software is needed, not only for the efficient processing of and access to the data but also for the effective extraction of the information needed in a user-friendly, consistent, and efficient manner. This enforces researchers and tourism actors in the use of tourism statistics and thus supports future research and decision making. To achieve this, we have developed a Tourism Information System application using Online Analytical Processing (OLAP), the "TSA-OLAP Model, " based on commercial "off-the-shelf" software to ensure worldwide access. Additionally, through the OLAP process, we probe deeply in TSA's information and identify extended methodological and/or theoretical issues of TSA. Thus, we discuss the future research and development of the TSA framework driven by the TSA-OLAP model.